Long term intravenous prostaglandin (epoprostenol or iloprost) for treatment of severe pulmonary hypertension. Issue 2 (1st August 1998) - Higenbottam, T; Butt, A Y; McMahon, A; Westerbeck, R; Sharples, L
Abstract : Objective: To investigate the relation between the severity of pulmonary hypertension and the outcome of medical treatment. Methods: 98 patients with primary pulmonary hypertension—nine (6%) with systemic disease and pulmonary hypertension and 39 (27%) with thromboembolic pulmonary hypertension—received medical treatment and were followed between 1982 and 1995. They were given long term intravenous prostaglandin treatment (either epoprostenol (n = 61) or iloprost (n = 13)) or conventional treatment with oral anticoagulants (n = 24) with or without calcium channel blockers. Event-free survival was measured to death or transplant surgery, or pulmonary thromboendarterectomy. Results: Prognosis (hazard ratio) was affected by: New York Heart Association grade, 1.52 (95% confidence interval 1.11 to 2.09); mixed venous oxygen saturation (Svo 2 %), 0.97 (0.95 to 0.98); cardiac index, 0.72 (0.49 to 1.06); mean right atrial pressure, 1.04 (1.01 to 1.07); and pulmonary vascular resistance, 1.02 (1.00 to 1.04). The median event-free survival time of patients with Svo 2 < 60% was 239 days (0 to 502) on conventional treatment (n = 22) and 585 days (300 to 870) on prostaglandin treatment (n = 42). No difference was seen in patients with Svo 2 ⩾ 60% between conventional treatment and prostaglandin treatment, survival being 1275 days (732 to 1818; (n = 48)) and 986 days (541 to 1431; n = 30)), respectively. Capacity for pulmonary vasodilatation did not predict outcome of treatment. Conclusions: Continuous intravenous prostaglandins were more effective than anticoagulants, with or without calcium channel blockers, in prolonging survival in patients with right heart failure. In these patients a capacity to vasodilate did not predict outcome from medical treatment.